IRAQ YOUTH TRENDS TOWARDS CELEBRITY ADVERTISEMENTS ON SOCIAL MEDIA : (A research taken from a Master Degree thesis) - Fathallah, Aqeel Tahseen; Al-Amery, Muhammad Hassan (ALBAHITH ALALAMI, 2020)
In the light of what is witnessing in the advertising arena of new ways and methods in delivering advertising message to consumers by finding new outlets to communicate with them especially through social networking sites, which became the first choice of advertising companies in order to spread its goods and services. These companies now are relying gradually on celebrities to appear with their products and goods to drive the audience's  attention towards them. The thesis aims to find out the attitudes of young people towards the the advertisements that show famous celebrities on social networking sites. The researcher used survey method which aims to record, analyze and interpret the phenomenon after collecting the necessary and sufficient data. The researcher also used the questionnaire method in his study. The researcher reached several results including: • Instagram is ranked first in terms of the most popular sites where celebrity advertisement are followed by The public,• the main reason behind following up on celebrities advertisements on social media is to get more information and data about the products.,• most of the celebrities whose heir ads are followed on social media are fashion and style celebrities.• the public's credibility about celebrity ads on social media is moderate.• The following audience of these ads was neutral in terms of products advertised by celebrities and was neutral in terms of their ads on social media in general,and one of the main disadvantages seen by the public regarding celebrities who advertise on social media for goods and products is that they advertise for money.